PERENCANAAN PERLINDUNGAN PILAR PADA JEMBATAN (Studi Kasus Bangunan Jembatan Trisula-Blitar) - Winda Ekasari, Gerard Aponno, Moch. Sholeh (Prokons: Jurnal Teknik Sipil, 2014)
Trisula bridge piers located at the delta of Brantas River do not have any protection from the stream of the river when flooding. The purpose of the design is to find out the scouring happens to piers caused by the river flow, to determine what kind of protection used to protect the piers, to plan the implementation method, to find out the cost, and the implementation time.Water discharge, pier dimensions, the span and depth of the river, the condition of piers, and velocity of the flow were needed to find out the scouring by Hydraulic Engineering Circular No. 18 application. The result was employed to determine the type of the protection. To find out the estimated costs were calculated through SNI-2012. Ms. Project were applied to find out the implementation time.Keywords: bridge, piers, scouring, partially grouted riprap